1995
DOI: 10.1002/j.1552-4604.1995.tb04998.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Cardiovascular Effects of H2‐Receptor Antagonists

Abstract: In vitro studies and animal experiments as well as clinical observations in humans concerning cardiovascular effects of H2-receptor antagonists have been published shortly after the development. Thus, clinical studies were performed to investigate these effects. The following review summarizes the results from in vitro studies up to the clinical investigations performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…Specifically, H 2 receptors promote inotropy, and H 2 antagonists such as cimetidine and ranitidine have been implicated with sinus bradycardia through this mechanism. 16 Patients with ranitidine-induced bradycardia have experienced symptoms with a single injection of ranitidine, on rechallenge, with oral administration, and even after several weeks of therapy. 17,18 In my patient, intravenous ranitidine for stress ulcer prophylaxis was begun at hospital admission and was continued through the resolution of his bradycardia, making ranitidine an unlikely cause of this adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, H 2 receptors promote inotropy, and H 2 antagonists such as cimetidine and ranitidine have been implicated with sinus bradycardia through this mechanism. 16 Patients with ranitidine-induced bradycardia have experienced symptoms with a single injection of ranitidine, on rechallenge, with oral administration, and even after several weeks of therapy. 17,18 In my patient, intravenous ranitidine for stress ulcer prophylaxis was begun at hospital admission and was continued through the resolution of his bradycardia, making ranitidine an unlikely cause of this adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…191 Histamine 2 receptors in the cardiovascular system regulate positive chronotropic and inotropic effects as well as stimulate vasodilation and slow arteriovenous node conduction. 192,193 In sepsis, histamine concentrations increase to maintain hemodynamic stability, thus H 2receptor antagonists may have a negative effect in septic patients. 192,193 Cardiovascular effects, such as bradycardia, have been reported with intravenous infusion of these agents; they may be more common with cimetidine, and may be related to the rate of infusion and/or dose.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…192,193 In sepsis, histamine concentrations increase to maintain hemodynamic stability, thus H 2receptor antagonists may have a negative effect in septic patients. 192,193 Cardiovascular effects, such as bradycardia, have been reported with intravenous infusion of these agents; they may be more common with cimetidine, and may be related to the rate of infusion and/or dose. 183,184,194 Bradycardia was reported in two children.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…In a previous report, the use of high-dose H2blocker was associated with several adverse effects such as bradycardia, sinus arrest, atrio-ventricular conduction disturbances, and cardiac decompensation [4]. However, another study reported that H2-blocker could modulate heart-rate variability, and has the possibility to inhibit the increase in the sinus rate and prevent ventricular ectopy [5].…”
Section: Introductionmentioning
confidence: 99%